Hubungan Praktik Pemberian Makan dengan Kejadian Picky Eater pada Anak Usia Toddler - Nurul Hijja; Agrina; Didi Kurniawan (Universitas Bengkulu, 2022)
Picky eater is an eating behavior disorder that occurs in toddlers appetite , refusing to be fed, picky eating and refusing to eat a varied menu behavior Picky eater that continues in the long term will cause growth and development disorders. Objective: To analyze the relationship between feeding practices and the incidence of picky eaters in toddlers. Methods: The research design used was descriptive correlation, with a cross sectional approach. The sample in this study amounted to 72 mothers who have toddler age children, which were taken using accidental sampling technique. The measuring instrument used is a questionnaire on maternal feeding practices and a questionnaire on picky eater that have been valid and reliable. Data were analyzed using chi-square test. Results: Chi-square showed that there was a significant relationship between feeding practices and the incidence of picky eaters age children toddler with pvalue (0.000) < (0.05). The majority of mothers with inappropriate feeding practices resulted in children experiencing picky eater (91.3%). So that the more inappropriate the mother's feeding practices are, the higher the risk of the child becoming a picky eater. Conclusion: Mothers who show inappropriate feeding practices in toddlers willbehavior picky eater.